Prevalence and severity of dental fluorosis among students from João Pessoa, PB, Brazil Prevalência e severidade de fluorose dentária em escolares da cidade de João Pessoa, PB, Brasil - Thiago Saads Carvalho; Helen Moura Kehrle; Fábio Correia Sampaio (Sociedade Brasileira de Pesquisa Odontológica, 2007)
The aim of this study was to determine the prevalence and severity of dental fluorosis among 12-15-year-old students from João Pessoa, PB, Brazil before starting a program of artificial fluoridation of drinking water. The use of fluoridated dentifrice was also surveyed. A sample of 1,402 students was randomly selected. However, 31 students refused to participate and 257 were not permanent residents in João Pessoa, thus leaving a final sample of 1,114 students. Clinical exams were carried out by two calibrated dentists (Kappa = 0.78) under natural indirect light. Upper and lower front teeth were cleaned with gauze and dried, and then examined using the TF index for fluorosis. A questionnaire on dentifrice ingestion and oral hygiene habits was applied to the students. The results revealed that fluorosis prevalence in this age group was higher than expected (29.2%). Most fluorosis cases were TF = 1 (66.8%), and the most severe cases were TF = 4 (2.2%). The majority of the students reported that they had been using fluoridated dentifrices since childhood; 95% of the participants preferred brands with a 1,500 ppm F concentration, and 40% remembered that they usually ingested or still ingest dentifrice during brushing. It was concluded that dental fluorosis prevalence among students in João Pessoa is higher than expected for an area with non-fluoridated water. However, although most students use fluoridated dentifrices, and almost half ingest slurry while brushing, the majority of cases had little aesthetic relevance from the professionals' point of view, thus suggesting that fluorosis is not a public health problem in the locality. O objetivo deste estudo foi determinar a prevalência e severidade de fluorose dentária em escolares de 12 a 15 anos de idade de João Pessoa, PB, Brasil antes da implantação de um programa de fluoretação de águas. O uso de dentifrício fluoretado também foi investigado. De 1.402 escolares aleatoriamente selecionados, 31 recusaram-se a participar, 257 não eram residentes permanentes na cidade, resultando em uma amostra final de 1.114 escolares. Dois cirurgiões-dentistas calibrados (Kappa = 0,78) realizaram exames clínicos sob luz natural indireta nos dentes anteriores superiores e inferiores limpos com gaze e secos, aplicando-se o índice TF para fluorose. Um questionário sobre ingestão de dentifrício e hábitos de higiene oral foi aplicado. Os resultados demonstram uma prevalência de fluorose acima do esperado (29,2%). A maioria dos casos foi TF = 1 (66,8%), e os mais severos foram TF = 4 (2,2%). A maioria dos estudantes informou que faz uso de dentifrícios desde a infância; 95% dos participantes preferiam marcas com 1.500 ppm F e 40% confirmaram que usualmente ingeriam ou ainda ingerem dentifrício durante a escovação. Conclui-se que a prevalência de fluorose entre estudantes de João Pessoa é acima do esperado para uma cidade sem fluoretação de águas. No entanto, apesar de a maioria dos estudantes usar dentifrícios fluoretados, e quase a metade deles ingerir dentifrício quando escova, a maioria dos casos foi de pouco comprometimento estético sob o ponto de vista dos profissionais, o que sugere que a fluorose não se constitui em um problema de saúde pública nesta localidade.